Formulation of Environmental, Social, and Governance (ESG) Concept Regulation in the Banking Sector as a Strategy to Realize Sustainable Development in Indonesia - Albertus Sentot Sudarwanto; Dona Budi Kharisma; Salsabila Adinda Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The increasing issue of the global environmental crisis has prompted the UN to launch 17 Sustainable Development Goals (SDGs). Although Indonesia has a strong commitment to achieving the SDGs, its implementation is still lagging behind, one of the reasons being the suboptimal application of Environmental, Social, and Governance (ESG) at the company level, especially in the banking sector. This creates uncertainty, implementation obstacles for companies, and opens up loopholes for ESG-washing practices. This study aims to formulate a regulatory formulation for the ESG concept in the banking sector as a strategy to accelerate sustainable development in Indonesia. The research method used is normative legal research that is prescriptive with a statutory approach and a conceptual approach. The types and sources of legal materials use primary legal materials and secondary legal materials. The results of the study conclude that an effective regulatory formulation is needed including a revision of POJK 51/POJK.03/2017 to require integrated reporting and adoption of the double materiality concept. In addition, it is recommended to strengthen the role of Good Corporate Governance (GCG), establish standard and measurable ESG reporting standards, require independent assurance (verification) of sustainability reports, and enforce legal sanctions against ESG-washing practices.